Prevalence and susceptibility pattern of Methicillin Resistant Staphylococcus aureus (MRSA) in Kashmir - Ahmad, S (Bangladesh Journal of Medical Science, 2013)
Background: Methicillin resistant Staphylococcus aureus (MRSA) is a multidrug resistant organism that threatens the effectiveness of antibiotics worldwide and is a threat in hospitals and long-term care settings. Aims: To determine the proportion of MRSA strains and their in vitro antibiotic susceptibility patterns against various antibiotics. Material and Methods: Different clinical specimens (n= 679) received at Al-Haram Diagnostic, Research and Training Center, Kashmir during a two year period commencing January, 2009 to December, 2010 were cultured, the isolates identified using standard microbiological techniques and their antibiotic susceptibilities determined. Results: Of the 679 specimens, Staphylococcus. aureus was isolated in 127 and 32 (25.2%) of these 127 were found be MRSA. No significant association with age or sex were observed in the MRSA positive specimens. MRSA were mainly isolated from burns, and skin and superficial soft tissue infections. MRSA isolates were found to be 100% sensitive to Vancomycin and 94%, 87%, 81%, 78% and 75% of isolates were resistant to Gentamycin, Tetracycline, Clindamycin, Erythromycin and Co-trimoxazole respectively. Conclusions: The relatively high proportion of MRSA and the associated antibiotic resistance seen in this study emphasizes the need for local or country based surveillance to characterize and monitor MRSA and to develop strategies that will improve MRSA treatment and control. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16663 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 427-431